2014
DOI: 10.1016/j.msea.2014.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the build orientation on the mechanical properties and fracture modes of SLM Ti–6Al–4V

Abstract: originates from the AM process. To understand the effect of the microstructure on the tensile properties, selective laser melted (SLM) Ti-6Al-4V samples built in three different orientations were tensile tested. The investigated samples were near fully dense, in two distinct conditions, as-built and stress relieved respectively. It was found that the build orientation affects the tensile properties, and in particular the ductility of the samples. The mechanical anisotropy of the parts was discussed in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
330
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 806 publications
(377 citation statements)
references
References 48 publications
29
330
3
15
Order By: Relevance
“…• Titanium alloys: Titanium alloy, specifically Ti-6Al-4V [72,[137][138][139][140][141][142][143], is the most investigated material for SLM process. Manufacturing titanium alloys via conventional methods is relatively difficult, since Ti is highly reactive and sensitive to chemical impurities, such as O, N and H. With this regard, SLM is superior to conventional manufacturing methods since the inert gas in the SLM chamber can provide a protective atmosphere.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…• Titanium alloys: Titanium alloy, specifically Ti-6Al-4V [72,[137][138][139][140][141][142][143], is the most investigated material for SLM process. Manufacturing titanium alloys via conventional methods is relatively difficult, since Ti is highly reactive and sensitive to chemical impurities, such as O, N and H. With this regard, SLM is superior to conventional manufacturing methods since the inert gas in the SLM chamber can provide a protective atmosphere.…”
Section: Materials Manufactured With Slmmentioning
confidence: 99%
“…The variation in build orientation aimed to analyse the possible effect of anisotropy on the tensile characteristics of the samples fabricated using laser beam melting. Due to the inherent layerby-layer fabrication methodology, it has been found that the build orientation can have an effect on the mechanical characteristics of the fabricated samples [21].…”
Section: Variation With Build Orientationmentioning
confidence: 99%
“…[12] Simonelli et al found no variation in elastic modulus of SLM Ti-6Al-4V with build orientation due to the weak a 0 texture of the as-built material. [13] These limited results suggest that for Ti-6Al-4V, there should be little elastic anisotropy of the material itself after SLM and subsequent stress relief.…”
Section: Introductionmentioning
confidence: 97%